(untitled) (Journal of Educational Sciences, 2016)
The article considers the issues of an emergence and development of the piano school in Kazakhstan. The acquisition of Kazakhstan’s independence and sovereignty, the democratic transformation in the socio-economic and spiritual spheres of Kazakh society, ever-challenging task of music education faced by educators, practitioners need to further develop work on the education of pianists professionals need to be improved in the development of national musical culture, continuous improvement of teaching and most of its scientific validity. In the practice of music education in Kazakhstan piano playing has become the most popular. Achieved unique results in the world, this kind of musical education is widespread in our country. Modern Kazakh piano art is one of the most interesting phenomena in the development of musical culture. It is heterogeneous and multi-piece: on the one hand, the process of its formation occurred, depending on the specific historical conditions of the development of culture, on the other – as a result of interaction of Russian, Western European cultures and traditions of the Kazakh national folklore. Two components of the Kazakh piano art – Performance and education – at all the evidence had not been considered in the course of a single cultural-historical development and have not received the relevant scientific and artistic appreciation. Review of the problem of formation and development of the piano school in Kazakhstan at the present stage is not possible without reference to the historical background of the occurrence of music education in the country. At the beginning of XX century Kazakhs, as well as other related peoples of Central Asia led a nomadic life. The originality of the nomadic Kazakh society was that of the city, urban life forms have not played it determines the cultural role. Professional music Kazakhs, like the other peoples of the East, was without music notes by modern definition, it is – the professional music of oral tradition. The beneficial effect on the development of musical environment in Orenburg had that beginning of the XIX century in the history of European and Russian culture is known as a rugged, lush flowering of piano art. Aesthetics performing romantic conquest of Europe. Music community was genuinely passionate about creativity Schubert, Chopin, Schumann, Liszt, Camille Saint-Saens and other composers-pianists, who actively promoted the new trends in music. The waves of this giant «tsunami» came to Kazakhstan with some delay. The trend of development of amateur music-making has brought the formation of social needs, without which the proper development of piano performance would be difficult. In Orenburg, Semipalatinsk open shops where you can buy sheet music. The growing interest in the art of music has caused the demand for musical instruments has led to the discovery of the city of shops selling pianos.